Analisis Partisipasi Perempuan Dalam Pekerjaan Sektor Informal Di Kompleks Punton Palangka Raya - Eriawaty; Emy Artuti (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2015)
Community in Punton Complex, Pahandut District of Palangka Raya Municipality, is known as group of people who tend to work in informal sectors, including all family members from parents to children. Women’s involvement in informal sector occupations is further elaborated in this research, to be specific on reasons why they chose jobs in informal sectors. From the results of this research, it is found out that (1) Women’s participation in informal sector occupations in Punton Complex is relatively high, almost all housewives and female teenagers work in this sector. (2) Women work in informal sector in Punton Complex are motivated by unemployed husbands because of illnesses or other causes, low household income yet high outcome, as an activity during spare time, to earn money, and to gain experiences. (3) The type of informal sector occupations mostly performed by women in Punton Complex is trading, either trading groceries or being street vendors in the market area and shops in Palangka Raya Municipality.